2022
DOI: 10.1038/s41467-022-28280-1
|View full text |Cite
|
Sign up to set email alerts
|

Inferring protein expression changes from mRNA in Alzheimer’s dementia using deep neural networks

Abstract: Identifying the molecular systems and proteins that modify the progression of Alzheimer’s disease and related dementias (ADRD) is central to drug target selection. However, discordance between mRNA and protein abundance, and the scarcity of proteomic data, has limited our ability to advance candidate targets that are mainly based on gene expression. Therefore, by using a deep neural network that predicts protein abundance from mRNA expression, here we attempt to track the early protein drivers of ADRD. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 43 publications
2
55
0
Order By: Relevance
“…However, protein alterations in small structures such as the synapse can be diluted in whole cell/tissue analyses. Furthermore, deep proteomic profiling of human brain can reveal changes in protein expression that are not highlighted by RNA expression analysis [ 19 , 20 ]. This highlights the importance of using well-characterised human samples for the development of comprehensive proteomic datasets.…”
Section: Introductionmentioning
confidence: 99%
“…However, protein alterations in small structures such as the synapse can be diluted in whole cell/tissue analyses. Furthermore, deep proteomic profiling of human brain can reveal changes in protein expression that are not highlighted by RNA expression analysis [ 19 , 20 ]. This highlights the importance of using well-characterised human samples for the development of comprehensive proteomic datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Cautions need to be taken to interpret the data about PICALM expression in human autopsy tissues. The results of PICALM expression are often based on the bulk tissue of human postmortem brains [ 32 , 33 , 124 ]. Since the cell type composition of brain tissue undergoes alterations during the progression of neurodegenerative disease, such bulk data may confound the interpretation of differences in gene expression between AD patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…During the progression of AD, PICALM mRNA expression levels are increased in the brain [ 32 , 124 ] and in the blood [ 125 ] of AD patients. In contrast, the PICALM protein level in the total bulk tissue is decreased in AD brains [ 33 ].…”
Section: Picalm and Alzheimer’s Disease Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, marked spatial, temporal, and quantitative differences between mRNA and protein expression make proteomic subtyping a potential source of unique biological insights [25,26]. Furthermore, compared to RNA differences, protein changes associate more strongly with AD clinical and pathological phenotypes, consistent with their being more proximate mediators of disease manifestations [27][28][29]. Using unbiased co-expression network analysis, we have demonstrated that the cortical brain regions of those with pathologically defined early-and late-stage LOAD feature a wide range of altered protein systems not observed in the transcriptome [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%